2022
DOI: 10.3390/polym14132651
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Strength and Failure Strain Distributions of Sheep Wool Fibers

Abstract: Sheep wool is an eco-friendly, renewable, and totally recyclable material increasingly used in textiles, filters, insulation, and building materials. Recently, wool fibers have become good alternatives for reinforcement of polymer composites and filaments for 3D printing. Wool fibers are susceptible to environmental degradation that could shorten their lifetime and limit applications. This study reports on the mechanical properties of sheep wool fibers under the impact of humid air and UV irradiation. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(138 reference statements)
0
5
0
1
Order By: Relevance
“…It should be noted that the mechanical properties of sheep wool are also affected by the conditioning process. Starkova et al [ 59 ] reported that the long-term conditioning of fibers in a humid environment and under UV irradiation resulted in a significant decrease in tensile strength and elastic modulus. In contrast (see Table 8 ), the elongation at break values for sheep wool and silk are significantly higher than those of other natural fibers.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the mechanical properties of sheep wool are also affected by the conditioning process. Starkova et al [ 59 ] reported that the long-term conditioning of fibers in a humid environment and under UV irradiation resulted in a significant decrease in tensile strength and elastic modulus. In contrast (see Table 8 ), the elongation at break values for sheep wool and silk are significantly higher than those of other natural fibers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, composite materials present complications for recycling. Starkova et al [6] dealt with the effect of the environmental degradation of wool, which can affect the life cycle and useful life of sheep wool fibers. They investigated the influence of moist air and UV radiation individually and synchronously using the two-parameter Weibull distribution [7].…”
Section: Thermal and Acoustic Insulationmentioning
confidence: 99%
“…Tests of the elastic modulus and strength of the fibers showed individual reductions in mechanical degradation characteristics (moisture-saturated fibers up to 43%, UV aging up to 50%), but the simultaneous action of both factors had an even worse effect. The study [6] is a demonstration of the applicability of the Weibull distribution for predicting the service life of sheep wool.…”
Section: Thermal and Acoustic Insulationmentioning
confidence: 99%
“…У процесі переробки вовни, починаючи з її миття, карбонізації, чесання, відбілювання тощо, міцність волокон зазвичай зменшується. На міцність вовни також впливають конституція тварини, її фізіологічний стан, індивідуальні властивості, умови годівлі та утримання (Starkova et at., 2022). Отже, вовна володіє цілим комплексом ознак, що характеризують її фізичні, а отжей технологічні властивості.…”
Section: вступunclassified